Efektivitas Pembelajaran Al-Quran Hadis Dalam Meningkatkan Kualitas Membaca Al-Quran Siswa Kelas VII Di MTs Tanjung Kasau - Kintara, Azlia Fasya; Alfiansyah, Muhammad; Purba, Fauzul Azmi; Fajri, Fadlan (LPPM Universitas Labuhanbatu, 2023)
The Qur'an is a revelation, kalam or word of Allah which contains teachings to be used as guidelines and guidance in the values of human life and all of nature. His teachings apply throughout time, since it was revealed until the end of time. While the hadith is everything that is based on the Prophet Muhammad. In the form of speech, deed, and determination (raqrir). Hadith is the second important source after the Qur'an which functions as an explanation (al-tabyin) of the Qur'an. Knowledge, understanding and implementation of religious values in the subject of the Qur'an-Hadith proves the occurrence of learning that is included in the cognitive, affective and psychomotor aspects. In the process, a teacher is very instrumental in achieving student achievement. This research is motivated by one of the student phenomena that many of them cannot read the Koran and even recognize hijaiyyah letters, therefore the teacher has a role to improve students' reading skills of the Koran. Another problem related to the reality of learning the Qur'an and hadith is the low interest and motivation of school and madrasah students to study the Qur'an and hadith. There is a tendency among students that learning the Qur'an and hadith is only a secondary goal of various other subjects taught in schools including religious schools or madrasas. As a result of the low interest and motivation in learning the Qur'an and hadith, it will certainly have an impact on the low ability of students to understand and interpret the verses of the Qur'an and the hadiths of the Prophet which they should have mastered.